Diagnosis and treatment of dermatofibrosarcoma protuberans. European consensus-based interdisciplinary guideline - Saiag, Philippe; Grob, Jean-Jacques; Lebbe, Celeste; Malvehy, Josep; del Marmol, Veronique; Pehamberger, Hubert; Peris, Ketty; Stratigos, Alexander; Middelton, Mark; Basholt, Lars; Testori, Alessandro; Garbe, Claus (European journal of cancer (1990), 2015)
Dermatofibrosarcoma protuberans (DFSP) is a skin fibroblastic tumour that is locally aggressive, with a tendency for local recurrence, but rarely metastasizes. A unique collaboration of multi-disciplinary experts from the European Dermatology Forum (EDF), the European Association of Dermato-Oncology (EADO) and the European Organization of Research and Treatment of Cancer (EORTC) was formed to make recommendations on DFSP diagnosis and treatment, based on systematic literature reviews and the experts’ experience. Diagnosis is suspected clinically and confirmed by pathology. Analysis by fluorescence in situ hybridisation (FISH) or multiplex reverse transcriptase-polymerase chain reaction (RT-PCR) to detect specific chromosomal translocations and fusion gene transcripts is useful to confirm a difficult DFSP diagnosis. Treatment is mainly surgical, with the aim to achieve complete resection of the tumour. In order to reduce the recurrence rate, the treatment of choice of DFSP seems to be Mohs’ micrographic surgery (MMS) and related variants. In hospitals where only standard histopathological procedures are available, standard excision with lateral safety margin of 3cm is advisable. Imatinib (Glivec®) is approved in Europe for the treatment of inoperable primary tumours, locally inoperable recurrent disease, and metastatic DFSP. Imatinib has also been given to patients with extensive, difficult-to-operate tumours for preoperative reduction of tumour size, but the usefulness of this attitude should be confirmed by clinical trials. Therapeutic decisions for patients with fibrosarcomatous DFSP should be primarily made by an interdisciplinary oncology team (‘tumour board’).